Low Urban Attractiveness of Edea in Cameroon: An Appraisal of Local Constraints - NDJEM, Marie louise Simone NYONKWE NGO; ENI, Ruth TUA; KOLA, Edinam; MOUPOU, Moise; AHOLOU, Coffi (Journal of Ecohumanism, 2025)
Edea is located at a strategic position at crossroads of significant urban centres such as Douala and Yaoundé. Edea’s evolution began with the construction of the hydroelectric power station in 1950, which attracted many large industrial establishments and agricultural developments. Many people got jobs, housing and camps were developed for workers, and schools and health centers were constructed. Sad to say, the economic crisis that struck Cameroon in the 1990s caused decline in productivity and closure of some of these industries leading to loss of jobs. Other neighbouring towns around Edea became points of interests as emerging urban centers with industrial and economic activities. Edea today can be described as a town, which has low urban attractiveness, as there are no significant changes compared with other towns in Cameroon giving its industrial and economic history. The aim of this study was to identify the indicators of its low urban attractiveness. A concurrent triangulation mixed-methods research design was used to address this research question and this was supported by documentary analysis. A household-based survey was used with a sample of 383 observations and semi-structured interviews with key informants were conducted. The key informants and survey showed contributing factors to the low attractiveness of Edea, including ethnic crisis, insecurity, inadequate economic development that is now over-shadowed by the informal sector, inadequate waste management, pollution, and a deteriorating local climate. However, with the development of undeveloped site tourism sites, and rehabilitation of infrastructure and equipment, Edea can return to becoming a city of attraction for residents.